인문교양 수업의 비교과 프로그램 운영 사례에 대한 연구 -팀 기반 독서토론 활동을 중심으로 - 김현주 (교양교육연구, 11(1), 2017)
본고에서는 교양필수 과목인 <인문학프로젝트>와 연계한 비교과 프로그램의 운영 현황을 소개하고 이 중, 팀 기반 독서토론 프로그램인 ‘인문학독서원정대’의 활동 성과와 함께 앞으로의 과제에 대해 살펴보았다. 본 활동은 정규 수업의 시간적, 공간적 제약을 벗어나 자유로운 독서토론 활동을 가능하게 함으로써 수업의 이해도를 높이고 학생들의 자기표현능력을 향상시키는 데 기여하였다. 또한 팀원 간 소통과 협력을 통해 사회구성원으로서 살아가는 데 필요한 갈등조정 방법을 체득할 수 있는 기회가 되었음을 확인할 수 있었다. 앞으로 이러한 성과를 바탕으로 효율적인 독서토론과 팀 활동 지원을 위한 기본적인 통합 지도안을 마련해 가야 할 것으로 본다. 또한 프로그램의 특성을 살린 만족도 조사를 실시하여 학생들의 요구를 프로그램 개선에 적극 반영해야 할 것이다. 특히 예산집행의 간소화, 전문 인력 보강 등 현실적인 문제들을 해결하여 학생들의 참여도를 높일 필요가 있다. 아울러 인문교육이 지식축적과 함께 삶의 현장에서 그 가치를 실현하는 일이 중요한 만큼 전체 학년을 대상으로 차별화된 교과-비교과 독서토론 활동 프로그램을 개발하여 학생들의 독서능력을 신장하고 협동을 기반으로 문제를 해결해 나가는 능력을 향상시킬 수 있도록 지원해야 할 것이다. 이는 외부적인 환경 변화를 떠나 지속적으로 다양한 인문교육의 장을 확대해 감으로써 급변하는 시대에 창의적으로 대응할 수 있는 인재를 양성해 가는 데 기여할 것으로 본다. This article has introduced the status of operating extra-curriculum programs connected to the <liberal arts project> as the required course for liberal arts, and from them, the activity outcome of the team-based reading discussion program, ‘liberal arts reading explorer’, as well as its tasks for the future are sought. These activities enable the free reading discussion activities by deviating the time and spatial restriction of regular classes to enhance the level of understanding of classes and contribute to enhance the self-expression of students. In addition, it is confirmed that it was an opportunity to acquire the conflict adjusting method required for living as a social constituent through communication and cooperation between team members. In the future, it is considered to prepare the basic integrated instruction scheme for efficient reading discussion and team activity support on the basis of such outcome. Furthermore, by implementing the survey on level of satisfaction with the characteristics of the program, it has to actively reflect the student demands for the improvement of program. In particular, there is a need to enhance the level of participation of students by resolving the realistic issues, such as, simplification of budget execution, reinforcement of professional human resources and etc. Also, since the realization of the value in the liberal arts education is important in the field of life together with the knowledge accumulation, the support has to be made to improve the competency in problem solution on the basis of cooperation by improving the reading competency of students by developing the differentiated extra-curriculum reading discussion activity program for the subject of entire students. It is considered to contribute to advance the human resources with creative response under the drastically changing era with the expansion of diverse fields of liberal arts education beyond the external environmental changes. KCI Citation Count: 11